Partial Experimental Findings on the Construal Base vs. Affixed Lexical Forms in Indonesian Measured through Drawing Duration - Thafhan Muwaffaq; Lusi Lian Piantari (Linguistik Indonesia, 2026)
Our study investigated whether Indonesian affixations affect speakers’ construal of base lexical forms. The participants in this study completed a drawing task with duration serving as an indirect index of construal. We hypothesized that affixed forms would require longer drawing durations due to the schematic meaning embedded by grammatical morphemes. Experiment 1 tested noun-based form batas, Experiment 2 tested verb-based form tumbuh, and Experiment 3 tested adjective-based form cepat, each with their respective affixed forms.  Experiment 1 yielded partial significant results: three affixed forms (batasan, pembatasan, and membatas) required significantly longer drawing durations than the base form. Experiment 2 showed no significant effects, while Experiment 3 suggested overall significance although post-hoc tests failed to validate specific pairwise differences. Despite mixed results, this study provides preliminary evidence that Indonesian derivational affixation influences construal, thus providing preliminary experimental evidence for construal effects of derivational morphology in Indonesian cognitive semantics.